2019
DOI: 10.1590/1980-5373-mr-2019-0247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Addition to Shielding Gas on Cooling Rates and in the Microstructure of Thin Sheets of Duplex Stainless Steel Welded by Pulsed Gas Tungsten Arc Welding Process

Abstract: The effect of the nitrogen content in the shielding gas and its effect on temperature distributions at the welded zone of thin sheets of duplex stainless steel have been evaluated. The duplex stainless steels have many features due to unique microstructural combination of austenite and ferrite grains. The phase balance can be easily shifted depending on the welding parameters. Two sheets were welded using pure argon and pure argon plus 2% of nitrogen as shielding gas. The thermal profile had shown that N 2-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…The addition of N 2 is known to increase the temperature of the weld pool as reported by [18][19][20]. The surface tension-driven Marangoni convection depends on the maximum temperature reached in the molten state.…”
Section: Effect On Geometrical Featuresmentioning
confidence: 87%
“…The addition of N 2 is known to increase the temperature of the weld pool as reported by [18][19][20]. The surface tension-driven Marangoni convection depends on the maximum temperature reached in the molten state.…”
Section: Effect On Geometrical Featuresmentioning
confidence: 87%
“…[36][37][38] Moreover, proper control of operating parameters will enable the production of robust joints with an appropriate ferrite-austenite balance. [39][40][41][42][43][44] According to various standards and research, it has been reported that austenite contents below 30% are inadequate for most industrial applications. [45,46] Zhang et al [47] conducted multipass welds on a UNS S31803 DSS pipe using GTAW.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of mixing 2% nitrogen added 98% argon as backing gas for greater than 10 mm thickness, improving the corrosion resistance (Sales et al, 2016). Furthermore, several authors reported utilising nitrogen in the shielding and backing gas, leading to an increase of the austenite formation and lower chromium nitrides in the weld metal microstructure (Baghdadchi et al, 2020;Betini et al, 2019;Gozarganji et al, 2021;Liu et al, 2020;Matsunaga et al, 2013;Muthupandi et al, 2005). In contrast, the unbalance A/F transformation still occurred even with mixing a small percentage of nitrogen in argon for shielding gas or backing gas because the solubility and diffusion kinetics of atomic nitrogen in the solid-state is not in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies on the detrimental phases such as chromium nitride and austenite precipitation in DSS while welding process has been reported (Baghdadchi et al, 2020;Betini et al, 2019;Gozarganji et al, 2021;Karlsson et al, 1995;Lippold & Kotecki, 2005;Liu et al, 2020;Matsunaga et al, 2013;Muthupandi et al, 2005;Ramirez et al, 2003), not much work has been done to simplify the DSS's welding method by reducing backing gas consumption. In this research, the authors simplified its method by varying sequences of backing gas.…”
Section: Introductionmentioning
confidence: 99%